Presentation: Andean Agriculture (I) - Flores Galindo, Alberto (1979)
The property structure has been the predominant concern in agrarian studies in Peru. In the 1920s —during the time of Mariátegui— this concern led to inquiring about the role played by the hacienda in the Peruvian agrarian process and perhaps as a priority, to show, in the style of Valcárcel or Castro Pozo, the persistence of the community despite the Republic.